Consumer protection Standards in Europe - Smyczek, Slawomir, ....- (Brazowinicza : Wydawnictwo PLACET, 2019)
Very interesting and practical book for consumers, managers as well researchers. This book is an up to date study treating about consumer rights protection. The reader can find there an explanation of fundamental concepts relating to consumer behavior, market rights, threats created by business, and then smoothly discover the most actual consumer protection issues and an European approach to increase the consumer rights protection and awareness. It is a definitely recommended to read and introduced in practice.
Keywords: Consumenten